2012
DOI: 10.1128/cvi.00064-12
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Immunodiagnostic Assay for Detection of 13 Streptococcus pneumoniae Serotype-Specific Polysaccharides in Human Urine

Abstract: gTo improve the clinical diagnosis of pneumococcal infection in bacteremic and nonbacteremic community-acquired pneumonia (CAP), a Luminex technology-based multiplex urinary antigen detection (UAD) diagnostic assay was developed and validated. The UAD assay can simultaneously detect 13 different serotypes of Streptococcus pneumoniae by capturing serotype-specific S. pneumoniae polysaccharides (PnPSs) secreted in human urine. Assay specificity is achieved by capturing the polysaccharides with serotype-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
142
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 40 publications
2
142
0
3
Order By: Relevance
“…In addition to the usual methods for diagnosing PP, a specially developed urine antigen test was used. This assay selectively detects antigens of the pneumococcal serotypes contained in PCV13 [71]. That allowed cases caused by vaccine serotypes (VT-PP) to be distinguished from those caused by non-vaccine serotypes, even in non-invasive pneumococcal pneumonia.…”
Section: Pcv13mentioning
confidence: 99%
“…In addition to the usual methods for diagnosing PP, a specially developed urine antigen test was used. This assay selectively detects antigens of the pneumococcal serotypes contained in PCV13 [71]. That allowed cases caused by vaccine serotypes (VT-PP) to be distinguished from those caused by non-vaccine serotypes, even in non-invasive pneumococcal pneumonia.…”
Section: Pcv13mentioning
confidence: 99%
“…A third analyst interpreted the results when the first two analysts did not agree. The UAD test is a Luminex technology-based multiplex UAD assay, which can detect simultaneously 13 different serotypes of S. pneumoniae (serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F and 23F) by capturing serotype-specific polysaccharides secreted in human urine [14]. The in vitro validation of the test (based on a subset of the current study population) and specificity determination in noninfected individuals has been reported elsewhere [14].…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…In preparation for a large randomised placebo-controlled double-blind trial [13], we evaluated the diagnostic properties and clinical utility of a novel serotype-specific urinary antigen detection (UAD) multiplex assay [14] for the identification of 13 serotype-specific polysaccharides of S. pneumoniae (serotypes 1, 3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F and 23F) in human urine samples in patients hospitalised with CAP. The 13 polysaccharide antigens correspond to the serotypes used in the 13-valent pneumococcal conjugate vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of efficacy became possible with the development of a serotype-specific urinary antigen detection assay. 22,23 Using this assay, we were able to evaluate a 13-valent pneumococcal conjugate vaccine (PCV13) for the prevention of vaccine-type invasive and noninvasive community-acquired pneumonia in adults 65 years of age or older.…”
mentioning
confidence: 99%